Dynamic shading of a building envelope based on rotating polarized film system controlled by one-dimensional cellular automata in regular tessellations (triangular, square and hexagonal). Issue 1 (January 2015) - Zawidzki, Machi
Highlights Cellular automaton (CA) based shading is contextualized as a daylight control system. Polarized film shading system (PFSS) based on opto-mechanical modules is introduced. Opacity of PFSS modules is a function of dihedral rotation of polarized film elements. PFSS in regular grids: triangular, square & hexagonal are discussed and illustrated. Visual attractiveness of emergent CA patterns (particles, solitons) is discussed.